The ‘cursed’ queen - Gergely Kiss (Medievalista)
Clemence, the daughter of Charles Martell of Anjou and Clemence of Habsburg, was born in Naples and became the wife of King Louis X of France in 1315. She was widowed the following year, and before her death in 1328, she witnessed the extinction of the male line of the Capetian dynasty. The period is rich in narrative sources, and this study seeks to answer the question of how they portrayed Clemence, how 'Hungarian' she really was, and what attracted the interest of chroniclers in the 'age of the cursed kings'.